(untitled) (Journal of Geography and Environmental Management, 2025)
This article examines the distribution characteristics of the soil cover in the city of Khromtau, located in the eastern part of the Aktobe region. A morphological description of the soil profile is provided, and it was determined that the soil type is dark chestnut carbonate with a medium loamy texture. Based on the results of analytical analysis, the physical and chemical properties of the soil were studied. It was found that natural and climatic conditions, especially the arid continental climate and mining activities, have a significant impact on the morphological and chemical composition of the soil. The agrochemical properties of the dark chestnut soils were analyzed. The amount of water-soluble salts in the soil was determined, and signs of salinization were clearly visible based on morphological indicators. The lower layers of the soil are characterized by a high level of alkalinity. In the composition of the soil water extract, the amount of sodium and sulfate ions was found to be high in the experimental samples, indicating the saline nature of the soil. The granulometric composition of the soil profiles was determined, showing that it varies with depth and influences agro-physical properties. According to the mechanical composition, these soils are dominated by medium loamy and loamy particles, indicating low water permeability and promoting the accumulation of salts in the lower layers.